ORAL CORRECTIVE FEEDBACK AND LEARNERS’ UPTAKE IN THE 5TH GRADE OF AN ELEMENTARY SCHOOL IN SURABAYA - Rieny Anasthasia; Josefa J. Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study is a qualitative study which aimed to know oral corrective feedback and learners’ uptake in the 5th grade of an elementary school. The source of data was the teacher’s talks with the students in class and the analysis was focused on teacher’s oral corrective feedback and learners’ uptake. In order to reach the research objectives, the writer used the theory of oral corrective feedback and learners’ uptake by Panova and Lyster (2002). From the study, the writer found that five out of seven types of oral corrective feedback were used by the teacher, namely Recast, Metalinguistic Feedback, Elicitation, Explicit Correction, and Repetition. Furthermore, types of learners’ uptake following the teacher’s corrective feedback were Self Repair, Peer Repair, Repetition, Same Error, Different Error, Partial Repair and Hesitation. It can be concluded that oral corrective feedback may lead the students to show signs of learning or understanding implied in the students’ reaction to the teacher’s feedback.